Pin chip = 3-iron [videorecording (DVD)] - Lee, Seung-yeon; Kim, Ki-dŏk, 1960-2020; Jaehee, 1980- (Sony Pictures Classics, 2005)
When a mysterious drifter breaks into a mansion, he discovers a lonely, beautiful woman trapped in an abusive marriage. When she escapes on the back of his motorcycle, their romantic adventures are just beginning.